The Effect of Physical Working Environment, Group Dynamics and Coping Strategies on English Lecturer’s Occupational Stress at Three Universities of North Sumatera - Rafida, Tien (Dinamika Ilmu, 2018)
The objectives of this research is to obtain information on the effect of physical working environments, group dynamics and coping strategies to occupational stress. Analysis unit is English lecturer’s of three Universities of North Sumatera in Medan, involving 251 English lecturer’s selected randomly. Data analysis applies lane analisys with SPSS program. Research findings show that physical working environment, group dynamics has direct effect to coping strategies, coping strategies has direct effect to occupational stress. Physical working environment and group dynamics through coping strategies has indirect effect to occupational stress. Based on the result of inferential study that occupational stress explainable by variable coping strategies, group dinamics and physical working environment. Equally physical working environment and group dynamics in good condition and supported by choice correct coping strategies, will result occupational stress to decline.